2021
DOI: 10.3390/cancers13215402
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Wheel Running Does Not Enhance Radiotherapy Efficiency in a Preclinical Model of Prostate Cancer: The Importance of Physical Activity Modalities?

Abstract: Physical activity is increasingly recognized as a strategy able to improve cancer patient outcome, and its potential to enhance treatment response is promising, despite being unclear. In our study we used a preclinical model of prostate cancer to investigate whether voluntary wheel running (VWR) could improve tumor perfusion and enhance radiotherapy (RT) efficiency. Nude athymic mice were injected with PC-3 cancer cells and either remained inactive or were housed with running wheels. Apparent microbubble trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Furthermore, in the present study, the combination of exercise with immuno-chemotherapy had no effect on apoptosis at D16, whereas we expected an increase in cell death markers such as Caspase 3. One study found a potentiation of apoptosis when exercise was combined with radiotherapy compared with radiotherapy alone in a prostate cancer model (34,37). In a patient-derived xenograft (PDX) non-small-cell lung cancer model, Martıń-Ruiz et al also found that exercise in combination with PD-1 blockade reduced tumor growth, exhibiting diminished tumor cell proliferation and increase of tumor necrosis.…”
Section: No Molecular Changes In Mc38 Cells With Combined Exercise An...mentioning
confidence: 99%
“…Furthermore, in the present study, the combination of exercise with immuno-chemotherapy had no effect on apoptosis at D16, whereas we expected an increase in cell death markers such as Caspase 3. One study found a potentiation of apoptosis when exercise was combined with radiotherapy compared with radiotherapy alone in a prostate cancer model (34,37). In a patient-derived xenograft (PDX) non-small-cell lung cancer model, Martıń-Ruiz et al also found that exercise in combination with PD-1 blockade reduced tumor growth, exhibiting diminished tumor cell proliferation and increase of tumor necrosis.…”
Section: No Molecular Changes In Mc38 Cells With Combined Exercise An...mentioning
confidence: 99%